Perlindungan Hukum Terhadap Kreditur Atas Debitur Asing yang di nyatakan Insolvensi oleh Putusan Pengadilan Indonesia - Kelvin, Edwar (Universitas Internasional Batam, 2019)
The fundamental reason for the Insolvency of Penaga Timur (M)  SDN.BHD Shipping Companies from Malaysia is because they did not submit Peace Proposals at the Creditor Meeting as stipulated in Law Number 37 of 2004 concerning Bankruptcy and PKPU, and at that time the Bankruptcy Institution was no longer accepting The peace between the creditor and the debtor, as a result, the Curator appointed by the court must immediately issue all the assets of the bankrupt debtor, but is constrained by the location of the bankrupt debtor's assets outside the territory of the Republic of Indonesia, and of course this is very detrimental to PT. WAS and PT UML as Creditors as Justice Seekers. Researchers conducted descriptive-exploratory research with a juridical-normative approach. From the results of the research that has been done, the researcher did not find a situation where the East Penol (M) SDN BHD insolvency was caused by the cash flow test approach method, or the balance sheet test or going concern value concept and also had no relation to the assessment of debtor financial ratios such as liquidity (liqidaty), solvency (solvability), profitability (profitability) and leverage as it applies in the Perspective of Bankruptcy Regime in general, and in this case the lack of regulation regarding the provisions of International Law relating to the Ordering of a Bankruptcy and / or Cross Border Insolvency in general. The curator has not been able to fulfill the rights of creditors for bankruptcy bodies outside the territory of the Republic of Indonesia.